2005
DOI: 10.1097/00019501-200509000-00011
|View full text |Cite
|
Sign up to set email alerts
|

A potent opiate agonist protects against myocardial stunning during myocardial ischemia and reperfusion in rats

Abstract: 2',6'-Dimethyltyrosine-D-Arg-Phe-Lys-NH2 provides a cardioprotective effect against myocardial ischemia and reperfusion in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 10 publications
3
14
0
Order By: Relevance
“…In contrast, in another study, SS-20, which has no scavenging ability, impeded myocardial stunning when administered upon reperfusion. This ability of SS-02 to prevent myocardial stunning has been confirmed in an in vivo rat model [66].These findings with SS peptides support the hypothesis that ROS play a major role in reperfusion-induced myocardial stunning.…”
Section: Mitochondria-targeted Peptide Antioxidantssupporting
confidence: 60%
“…In contrast, in another study, SS-20, which has no scavenging ability, impeded myocardial stunning when administered upon reperfusion. This ability of SS-02 to prevent myocardial stunning has been confirmed in an in vivo rat model [66].These findings with SS peptides support the hypothesis that ROS play a major role in reperfusion-induced myocardial stunning.…”
Section: Mitochondria-targeted Peptide Antioxidantssupporting
confidence: 60%
“…The multiple injection paradigm was used, because there is a biphasic ROS production and sustained CD36 expression in post-ischemic brain (1,26). The dosage of SS31 used in the present study was based on the dosage previously used in protection against myocardial ischemia (22) and in a model of neurodegeneration (27).…”
Section: Drug Treatmentsmentioning
confidence: 99%
“…Unlike other antioxidants, the SS peptides target mitochondria and protect mitochondria against mitochondrial permeability transition, swelling, and cytochrome c release (2) and prevent t-butylhydroperoxide-induced apoptosis (20). These peptide antioxidants are very effective in preventing myocardial stunning and reducing infarct size following cardiac ischemia reperfusion (2,(21)(22)(23). To exploit an antioxidant approach by targeting CD36, the present study investigated whether the SS31 antioxidant peptide attenuates cerebral ischemia-induced injury and whether the peptide-induced neuroprotection involves the down-regulation of CD36 expression and function.…”
mentioning
confidence: 99%
“…Previously we showed that a potent opioid peptide, 2 0 ,6 0 -dimethyl-tyrosine (Dmt)-D-Arg-Phe-Lys-NH 2 (Dmt-DALDA or SS-02) , could prevent myocardial stunning in the isolated guinea pig heart [1] and in a rat ischemiareperfusion model [2]. Opioids, including morphine, have been shown to provide cardioprotection during ischemia [3].…”
Section: Introductionmentioning
confidence: 99%